Red discoloration of urine caused by Serratia rubidae: A rare case - Kumar, Simit (Medknow Publications & Media Pvt Ltd, 2013)
There have been only a few reported human cases of infections caused by Serratia rubidae in literature. Among these sparse cases there is only one reported case of urinary tract infection (UTI) due to S. rubidae in literature. The organism is known to produce a red pigment known as prodigiosin. We report a case of UTI caused by S. rubidae in a diabetic patient who presented with burning micturition and reddish discoloration of urine, which on laboratory diagnosis, was proved to be due to the reddish pigment produced by the organism. This case report highlights that this rare organism might be associated with UTI leading to reddish discoloration of urine.